Congruent population genetic structure but differing depths of divergence for three alpine stoneflies with similar ecology and geographic distributions. (17th December 2018) - Hotaling, Scott; Giersch, J. Joseph; Finn, Debra S.; Tronstad, Lusha M.; Jordan, Steve; Serpa, Larry E.; Call, Ronald G.; Muhlfeld, Clint C.; Weisrock, David W.
Abstract: Comparative population genetic studies provide a powerful means for assessing the degree to which evolutionary histories may be congruent among taxa while also highlighting the potential for cryptic diversity within existing species. In the Rocky Mountains, three confamilial stoneflies ( Zapada glacier, Lednia tumana, and Lednia tetonica ; Plecoptera, Nemouridae) occupy cold alpine streams that are primarily fed by melting ice. Lednia tumana and L. tetonica are sister species diagnosed from systematic morphological differences, and they are endemic to areas surrounding Glacier National Park and Grand Teton National Park, respectively, in the U.S. Rocky Mountains. Zapada glacier is also present in alpine streams from Glacier National Park to the Teton Range, sometimes co‐occurring with either Lednia species. We used mitochondrial sequence data to clarify species boundaries, compare population genetic patterns, and test demographic models in a coalescent framework for the three stoneflies. We addressed four questions: (1) Is there genetic support for the morphology‐based species boundaries in Lednia ? (2) Is there genetic support for cryptic, or as‐yet undescribed, diversity within Z. glacier ? (3) Do similar geographic distributions and ecological requirements yield spatial congruence of genetic structure between high‐elevation Lednia and Z. glacier populations? (4) Is there evidence for contemporary gene flow among isolated populations in either group? Our results supported the existing taxonomy with Z. glacier and the two Lednia species differing in their depths of divergence among study regions (e.g. maximum sequence divergence within Z. glacier = 1.2% versus 5% between L. tumana and L. tetonica ). However, spatial population genetic patterns were broadly congruent, indicating stonefly populations isolated on mountaintop islands. Coalescent modelling supported the possibility of rare, extremely limited contemporary gene flow among Z. glacier populations, with no support for gene flow between L. tumana and L. tetonica . The focal stoneflies and associated assemblages occupy the highest elevation, coldest permanent alpine streams in the study region. This lotic habitat type faces an uncertain future under a diminishing alpine cryosphere. Given spatial congruence of genetic structure demonstrating unique biodiversity associated with individual alpine islands, we encourage conservation management strategies be developed and applied at corresponding spatial scales.